D‐AKAP2:PKA RII:PDZK1 ternary complex structure: Insights from the nucleation of a polyvalent scaffold. (5th December 2014) - Sarma, Ganapathy N.; Moody, Issa S.; Ilouz, Ronit; Phan, Ryan H.; Sankaran, Banumathi; Hall, Randy A.; Taylor, Susan S.
Abstract A‐kinase anchoring proteins (AKAPs) regulate cAMP‐dependent protein kinase (PKA) signaling in space and time. Dual‐specific AKAP2 (D‐AKAP2/AKAP10) binds with high affinity to both RI and RII regulatory subunits of PKA and is anchored to transporters through PDZ domain proteins. Here, we describe a structure of D‐AKAP2 in complex with two interacting partners and the exact mechanism by which a segment that on its own is disordered presents an α‐helix to PKA and a β‐strand to PDZK1. These two motifs nucleate a polyvalent scaffold and show how PKA signaling is linked to the regulation of transporters. Formation of the D‐AKAP2: PKA binary complex is an important first step for high affinity interaction with PDZK1, and the structure reveals important clues toward understanding this phenomenon. In contrast to many other AKAPs, D‐AKAP2 does not interact directly with the membrane protein. Instead, the interaction is facilitated by the C‐terminus of D‐AKAP2, which contains two binding motifs—the D‐AKAP2AKB and the PDZ motif—that are joined by a short linker and only become ordered upon binding to their respective partner signaling proteins. The D‐AKAP2AKB binds to the D/D domain of the R‐subunit and the C‐terminal PDZ motif binds to a PDZ domain (from PDZK1) that serves as a bridging protein to the transporter. This structure also provides insights into the fundamental question of why D‐AKAP2 would exhibit a differential mode of binding to the two PKA isoforms.